Cress eaudiobook - Meyer, Marissa (The Lunar Chronicles, 2014)
The #1 New York Times Bestselling Series! In this third book in Marissa Meyer's bestselling Lunar Chronicles series, Cinder and Captain Thorne are fugitives on the run, now with Scarlet and Wolf in tow. Together, they're plotting to overthrow Queen Levana and prevent her army from invading Earth. Their best hope lies with Cress, a girl trapped on a satellite since childhood who's only ever had her netscreens as company. All that screen time has made Cress an excellent hacker. Unfortunately, she's being forced to work for Queen Levana, and she's just received orders to track down Cinder and her handsome accomplice. When a daring rescue of Cress goes awry, the group is splintered. Cress finally has her freedom, but it comes at a higher price than she'd ever expected. Meanwhile, Queen Levana will let nothing prevent her marriage to Emperor Kai, especially the cyborg mechanic. Cress, Scarlet, and Cinder may not have signed up to save the world, but they may be the only hope the world has.